2018
DOI: 10.24085/jsaa.v6i1.3066
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Student (Dis)engagement: Retention Officers’ Experiences at the Cape Peninsula University of Technology

Abstract: Most first-year university students experience serious academic and adjustment challenges, which remain undetected until it is too late to provide meaningful intervention. Universities are therefore developing academic support systems that can assist in identifying students who experience learning challenges early on, and provide quality first-year experiences that ensure that first-year students adapt, engage and succeed at the university. Such student academic support systems should provide resources that de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Most of the 121 articles from CAS confirmed that African student affairs practitioners are primarily involved in learning-assistance programmes. This task is indispensable to student success (De Klerk et al, 2017;Scott, 2018;Strydom et al, 2017) and retention (Mkonto, 2018), especially in terms of first-year student engagement (Faroa, 2017;Mkonto, 2018;Schreiber & Yu, 2016). In addition, learning-assistance programmes also place emphasis on mathematics (Jacobs & Pretorius, 2016), generic skills in the medical curriculum (Jama, 2016), and at-risk students (Mayet, 2016).…”
Section: Learning-assistance Programmesmentioning
confidence: 99%
“…Most of the 121 articles from CAS confirmed that African student affairs practitioners are primarily involved in learning-assistance programmes. This task is indispensable to student success (De Klerk et al, 2017;Scott, 2018;Strydom et al, 2017) and retention (Mkonto, 2018), especially in terms of first-year student engagement (Faroa, 2017;Mkonto, 2018;Schreiber & Yu, 2016). In addition, learning-assistance programmes also place emphasis on mathematics (Jacobs & Pretorius, 2016), generic skills in the medical curriculum (Jama, 2016), and at-risk students (Mayet, 2016).…”
Section: Learning-assistance Programmesmentioning
confidence: 99%
“…A great number of learners have individual and contextual motives for leaving school and this is a sign of disengagement from school and is a quickly developing occurrence [ 5 ] while it is a critical problem that ought to be taken more seriously. Engagement in the educational environment is vital [ 6 , 7 , 8 ]. Indeed, engagement is a crucial concept connected to education and educational achievements like better scores, frequencies of completion, and success test results (9].…”
Section: Introductionmentioning
confidence: 99%
“…Campus climate, sense of belonging, ethnicity and socioeconomic factors affects student retention and engagement especially with first-generation students who are reported to having lower retention and engagement [2]. Access to information and services as well as caring retention officers are identified as resources necessary for first-year student retention [3].…”
Section: Introductionmentioning
confidence: 99%